1.Wyznacz liczbę a,mając dany pierwiastek równania.
a)2(2y-3)-4(3y+2)=4-a y=-1
b)2(z-1)-az=-12-(5+2z) z=1
c)12x+2(x+1)=a(x+2)+14
2.Rozwiąż równania.
a)x+15=8⅓
b)12,4-x=20
c)2x+5=15 3/4
d)-3x=3 3/4
e)2(3x-4)=10
f)-3(5+2x)=15
g)4(x+3)-2=-6
h)30-10(2-3x)=-50
3-//-.
a)2(3x+4)-3(5x-6)+4(7x+8)=115
b)-0,8(10-2x)+1,2(x-20)+1/5x=-58
c)x(x-5)-x(x+4)=-63
4.-//-.
a)6x-7(11+2x)+2=-4(15-x)+3x
b)3(5x+3)=7(x+5)-3(2-x)
c)2(x-1)+4(x-3)=-3(x-2)+9x
d)5x-3(6-8x)=x-7(x+4)
e)2x+8(2x-3)-6(x-3)=5(3x+1)+2x-11
f)3(2x+3)-5(x-2)-4(x+7)=3
g)6(3,5-1,2x)=5(-3,5x+1,2)+0,3x

1

Odpowiedzi

2010-02-11T14:37:46+01:00
1.Wyznacz liczbę a,mając dany pierwiastek równania.
a)2(2y-3)-4(3y+2)=4-a y=-1
4y-6-12y-8 = 4-a
-8y - 14 = 4-a
-8 * (-1) -14 = 4-a
8 -14 -4 = -a
-10 = -a / : (-1)
10 = a
a = 10

b)2(z-1)-az=-12-(5+2z) z=1
2z - 2 -az = -12 -5-2z
2z+2z - az = -12 -5 +2
4z - az = -15
4 * 1 - a *1 = -15
4 -a = -15
-a = -15 -4
-a = -19 / :(-1)
a = 19

c)12x+2(x+1)=a(x+2)+14 (nie ma podanej wartości a)
12x +2x +2 = ax + 2a
14x -ax -2a = -2

2.Rozwiąż równania.
a)x+15=8⅓
x = 8⅓ - 15
x = -6 ⅔

b)12,4-x=20
-x = 20 - 12,4
-x = 7,6 / :(-1)
x = -7,6

c)2x+5=15 3/4
2x = 15 3/4 -5
2x = 10¾ / :2
x = 5 ⅜

d)-3x=3 3/4
-3x = 3 ¾ /: (-3)
x = ¹⁵/₄ * (⅓)
x = - 1¹/₄

e)2(3x-4)=10
6x - 8 = 10
6x = 10+8
6x = 18 / : 6
x = 3

f)-3(5+2x)=15
-15 -6x = 15
-6x = 15 + 15
-6x = 30 / : (-6)
x = -5

g)4(x+3)-2=-6
4x + 12 -2 = -6
4x = -6 -12 +2
4x = -16 / : 4
x = -4

h)30-10(2-3x)=-50
30 -20 + 30x = -50
30x = -50+20 - 30
30 x = -60 / : 30
x = -2

3-//-.
a)2(3x+4)-3(5x-6)+4(7x+8)=115
6x + 8 - 15x +18 + 28x + 32 = 115
6x-15x+28x = 115 -8-18-32
19 x = 57 / :19
x = 3

b)-0,8(10-2x)+1,2(x-20)+1/5x=-58
-8 + 1,6x + 1,2 x -24 + 0,2 x = -58
1,6x+1,2x+0,2x = -58+8+24
3x = -26 / :3
x = - 8 ⅔

c)x(x-5)-x(x+4)=-63
x² - 5x - x² - 4x = -63
-9x = -63 / :(-9)
x = 7

4.-//-.
a)6x-7(11+2x)+2=-4(15-x)+3x
6x-77-14x+2 = -60 + 4x + 3x
6x-14x - 3x-4x = -60 + 77-2
-15x = 15 / (-15)
x = -1

b)3(5x+3)=7(x+5)-3(2-x)
15x + 9 = 7x + 35 -6 + 3x
15x-7x-3x = 35-6-9
5x = 20 / : 5
x = 4

c)2(x-1)+4(x-3)=-3(x-2)+9x
2x - 2 + 4x - 12 = -3x +6 + 9x
2x+4x+3x-9x = 6+12+2
0 = 20 równanie sprzeczne

d)5x-3(6-8x)=x-7(x+4)
5x - 18 + 24x = x -7x-28
5x +24x - x + 7x = -28+18
35x = -10 / 35
x = -²/₇

e)2x+8(2x-3)-6(x-3)=5(3x+1)+2x-11
2x +16x - 24-6x+18 = 15x +5 +2x -11
2x+16x-6x-15x-2x = 5-11+24-18
-5x = 0 / : (-5)
x = 0

f)3(2x+3)-5(x-2)-4(x+7)=3
6x + 9 - 5x +10 - 4x -28 = 3
6x-5x+4x = 3-9-10+28
5x = 12 / : 5
x = 2 ²/₅

g)6(3,5-1,2x)=5(-3,5x+1,2)+0,3x
21 - 7,2x = -17,5x +6 + 0,3x
-7,2x +17,5x - 0,3x = 6 -21
10x = -15 / : 10
x = -1,5
5 4 5